The pharmacological treatment of acute vestibular syndrome - Viola, Pasquale; Gioacchini, Federico Maria; Astorina, Alessia; Pisani, Davide; Scarpa, Alfonso; Marcianò, Gianmarco; Casarella, Alessandro; Basile, Emanuele; Rania, Vincenzo; Re, Massimo; Chiarella, Giuseppe (Frontiers in Neurology, 2022)
AVS represents a clinical picture that involves urgent management due to the important procession of symptoms accompanying the event, which can be positively or negatively influenced by therapeutic choices and intervention timing. This forces a differential diagnosis and therapeutic choices to be made in conditions that are not always favourable and often not in the specialist field. In this work, we will examine in detail the pharmacological therapeutic possibilities, correlating them to the differential and, as far as possible, to the etiological diagnosis. In particular, the pharmacological possibilities for the two main conditions we can face will be investigated: vestibular neuritis and posterior circulation stroke.